Burkina Faso : Background Papers and Statistical Update. (IMF Staff Country Reports; Country Report ;, 1996)
This Background Papers and Statistical Update analyzes economic and financial developments in Burkina Faso during 1991-95. Real GDP growth averaged 2.3 percent per year during 1990-94. This outcome represented a substantial decline in real GDP per capita income. Growth in agricultural production declined markedly after 1991, when a bumper crop boosted output in the primary sector by more than 20 percent. Gold production in the existing semi-industrial mines took a downward turn in 1994, as the yield of several arteries started to diminish.